The effect of inlet flow distortion on installed gas turbine performance. - Triantafyllou, Theodoros (Cranfield University, 2018)
Military aircraft are often subjected to severe flight manoeuvres with high Angles of Attack (AOA) and Angles of Sideslip (AOSS). These flight attitudes induce non-uniform in flow conditions to their installed gas turbine engines which may include distortion of inlet total pressure and total temperature at the Aerodynamic Interface Plane (AIP). When the downstream compression system of the engine experiences such distorted inflow conditions its operation is significantly affected in that its aerodynamic performance is reduced along with its stall margin. Also the blade stress levels of the compression system increase and vibration becomes an issue. A large, complex facility is required to accurately test how the actual engines response to such distorted conditions. In addition to the engine support facilities, a full-scale inlet is needed to house the engine and a large secondary air supply system is needed to generate flight speed and altitude conditions relative to the inlet. As it can be easily imagined, the cost of this type of full scale testing is remarkably high. The objective of the present study is to develop a numerical method for the estimation of the installed gas turbine engine performance variations due to airflow distortion. This method will also provide the means to assess the compatibility of an airframe-engine set at a specific operating envelope, given the geometry of the upstream intake and the performance simulation model of the under examination gas turbine engine. In the present work, the distorted conditions at the interface between the intake and the engine have been numerically calculated with Computational Fluid Dynamics (CFD), where 27 different aircraft flight attitudes have been tested. As a baseline set of airframe-engine, were chosen an airframe inspired by the General Dynamics/LMAERO F-16 aircraft, equipped with a Pratt and Whitney F100-PW-229-like gas turbine engine. Also, the specified flow field was resolved by a commercial CFD code. The steady state total pressure distortion induced to the AIP due to the aircraft's flight attitude was estimated in terms of distortion descriptors. These parameters were then correlated to the surge margin of the downstream compression system. Following this methodology, it was concluded whether each one of the tested flight attitudes induced enough distortion to the AIP so as to surge the engine's FAN. Also the engine's performance variations due to airflow distortion have been also estimated in terms of net thrust changes. The obtained results justify the anticipated behaviour of the engine with degraded performance, in terms of resulted net thrust, when the aircraft flies with Angle of Sideslip (AOSS). Having the FAN shaft rotational speed as the controlled parameter, the net thrust percentage change between the uninstalled condition of the engine with rather uniform inflow and that when the engine is installed and exposed to different flight attitudes varies between -1.76% to -22.56% depending on the flight Mach number and the aircraft's flight attitude. Finally, all the results were combined and performance maps have been created that correlate the aircraft's flight attitude with the engine's net thrust.
Keywords: Airflow distortion; total pressure distortion; aircraft intake; intake pressure recovery; distortion descriptors; gas turbine performance; surge margin; fan stability